Ã˜RESTAD: RE.SCALED - Marques, Ana Catharina Moreira (Revista Estética e Semiótica, 2012)
Ã˜RESTAD: RE.SCALED is a communication platform between Ã˜restad and the centre of Copenhagen, bringing a sense of connection between the two areas. The service uses the city as a platform for pop-up information about different places of interest or activities in Ã˜restad. Providing a travel map, the service visualizes the travel time to arrive at the location. It is not one time intervention, but something that provides a constant loop of activities in order to create a consistent flow of people to places ”“ bringing consumers and activity to the area.